Apply the trig identity:# cos 4x = 2cos^2 2x - 1.##f(x) = cos 2x + 2cos^2 2x - 1 = 0#Call cos 2x = t, we have to solve the quadratic equation:

2t^2 + t - 1 = 0

Since (a - b + c) = 0, the shortcut gives: #t = - 1# and #t = -c/a = 1/2#

a. #cos 2x = t = -1 #--> #2x = +- pi# --> #x = +- pi/2#b. #cos 2x = t = 1/2# --> #2x = +- pi/3# --> #x = +- pi/6#Within interval #(-pi, pi),# there room 6 answers:#+- pi/2 ; +- pi/3 and also +- pi/6#Check by calculator:#x = pi/2# -> cos 2x = cos pi = -1 ; cos 4x = cos 2pi = 1 --> --> f(x) = -1 + 1 = 0. OK#x = pi/6# --> #cos 2x = cos pi/3 = 1/2# ; #cos 4x = cos (2pi)/3 = -1/2#--># f(x) = 1/2 - 1/2 = 0.# OK#x = pi/3# --> cos 2x = cos (2pi)/3 = 1/2 ; cos 4x = cos (4pi)/3 = - 1/2f(x) = 1/2 - 1/2 = 0. OK




You are watching: Find all solutions to the equation in the interval [0, 2π). cos 4x - cos 2x = 0

Answer attach
*

Alan P.
Aug 22, 2015

#color(blue)(x= pi/6+npi)color(white)("XX")orcolor(white)("XX")color(blue)(x = (5pi)/6+npi)color(white)("XX")orcolor(white)("XX")color(blue)(x =pi/2+npi)##color(white)("XXXXXXXX")AA n in ZZ#


Explanation:

Let #theta = 2x#

#cos(2x)+cos(4x)=0##color(white)("XXXX")#becomes#cos(theta)+cos(2theta) = 0#

By twin angle formula#color(white)("XXXX")cos(2theta) = 2cos^2(theta)-1#

So#cos(theta)+(2cos^2(theta) -1) = 0#

Rearranging#2cos^2(theta)+cos(theta)-1 = 0#

Factoring#(2cos(theta)-1)(cos(theta)+1) = 0#

#rArrcolor(red)(cos(theta) = 1/2)color(white)("XXXXXXXXXXXX")orcolor(white)("XXX")color(blue)(cos(theta)=-1)#

if restricted to #theta in <0,2pi>##color(red)(theta = pi/3 or theta=(5pi)/3)color(white)("XXXXXXXXXXX")orcolor(white)("XXXX")color(blue)(theta=pi)#

or in general (with #n in ZZ#)#color(red)(theta = pi/3+n2pi or theta=(5pi)/3+n2pi)color(white)("XXX")orcolor(white)("XXXX")color(blue)(theta=pi+2pi)#

Since #theta = 2x##x= pi/6+npi or x = (5pi)/6+npicolor(white)("XXXXX")orcolor(white)("XXXX")x =pi/2+npi#


Answer link
*

Nghi N
Apr 17, 2017

#pi/2 + 2kpi##(3pi)/2 + 2kpi##pi/6 + (2kpi)/3##pi/2 + (2kpi/3)#


Explanation:

Apply trig identity: #cos a + cos b = 2cos ((a + b)/2)cos ((a - b)/2)#In this case:#cos 2x + cos 4x = 2cos 3x.cos x = 0#Either cos x or cos 3x have to be zero.

a. Cos x = 0 --> Unit circle offers 2 solutions:#x = pi/2 + 2kpi#, and #x = (3pi)/2 + 2kpi#b/ cos 3x = 0 --> unit circle provides 2 solutions:#3x = pi/2 + 2kpi# --> #x = pi/6 + (2kpi)/3##3x = (3pi/2) + 2kpi# --> #x = pi/2 + (2kpi)/3#


Answer connect
Related inquiries
view all concerns in fixing Trigonometric Equations
influence of this inquiry
30987 views roughly the civilization
*



See more: More Questions About Mysterious Walmart Underground Tunnels Youtube

You deserve to reuse this prize an innovative Commons license